FLEXIBLE TECHNOLOGIES OF UNIVERSITY MANAGEMENT AS A TOOL TO INCREASE THEIR COMPETITIVENESS - Grishnova O. A.; Azmuk N. A.; Kuklin O. V. (Scientific Journal of Pedagogy and Economics, 2019)
Higher education faces global challenges caused by the dynamic change of the socium itself and the educational environment under the influence of globalization and extensive digitization of the society. The labor market requires the formation of a new generation of professionals capable of effective development and self-realization. The main problem that impedes the development of the Ukrainian education is the excessive bureaucratization of the educational process in universities where innovations do not find their practical implementation. This makes the higher education system unresponsive to external changes, which leads to the production and transfer of redundant and irrelevant knowledge for modern business environment. The above-mentioned factors determine the low level of competitiveness of Ukrainian higher education institutions. In this regard, there is a need to introduce Scrum management technology in the university education, based on the effective interaction of all participants of the educational process with a prominent level of flexibility and adaptability. Theoretical and methodological base of the article - conceptual positions and researches of experts on flexible technologies of management. Based on the results of the study, the authors formed the main provisions of the Uniscrum. The article deals with the crucial problems in the field of higher education. The employment of flexible Scrum technology in the management of higher education institutions to increase the efficiency of their activities is justified. The relevance of the values and principles of Agile flexible approach to the activities of universities in Ukraine is investigated. Authors’ definition of "Uniscrum" is proposed. The functions and principles of Uniscrum in relation to the management of the activities of universities are formulated. The key approaches to the use of Uniscrum are defined. The introduction of Uniscrum management technology in higher education as a project approach to managing the training of highly skilled professionals at universities will contribute to the effectiveness of educational activities, since it will provide the production and transfer of valuable professional knowledge for modern business.